Clinical aspects of cutaneous lupus erythematosus - Elmgren, Julia; Nyberg, Filippa (Frontiers in Medicine, 2023)
Lupus erythematosus (LE) is an autoimmune inflammatory disease with a wide clinical spectrum from life-threatening multi-organ inflammation in systemic lupus erythematosus (SLE) to limited skin disease in cutaneous LE (CLE). The etiology of CLE is still not fully understood but a multifactorial genesis with genetic predisposition and certain environmental factors as triggers for the development are generally accepted features. Lesions can be induced and aggravated by UV-irradiation and smoking is linked to more severe forms of skin disease and to co-morbidity. Drugs, including many common medicines like antihypertensives, are known to induce subacute CLE (SCLE). The mechanisms involved have recently been shown to be part of the IFN-I pathway and new, specific treatments are currently in clinical trials. CLE is currently classified in subtypes based on clinical presentation and duration into acute CLE (ACLE), SCLE, and chronic CLE (CCLE). Distinct subtypes can be seen in individual patients or coexist within the same patient. Because of the confluent and overlapping picture between these subsets, serology, and histopathology constitute an important role guiding towards correct diagnose and there is ongoing work to update the classification. The Cutaneous Lupus Area Severity Index (CLASI) is a validated tool to measure activity and damage both in clinical trials but also for the clinician to evaluate treatment and follow the course of the disease among patients. CLE is known to have substantial impact on the life of those affected. Several tools have been proposed to measure QoL in these patients, currently Skindex-29 is probably the most used. Patient education is an important part of prevention of flares, including UV-protection and smoking cessation. First-line treatment includes topical corticosteroids as well as topical calcineurin inhibitors with the addition of systemic treatment with antimalarials in more severe or therapy resistant cases. Treatment specifically targeting CLE has been lacking, however novel potential therapies are in later phase clinical trials. In this review we aim to describe the different subsets of the cutaneous form in LE with focus on clinical aspects.